Implementasi Sistem Pendukung Keputusan Berbasis Topsis untuk Optimalisasi Rotasi dan Promosi Karyawan di Bidang Marketing dan Penjualan - Sitanggang, Lestari Pratiwi; Trisanti, Ayu; Sirait, Ritawati; Simbolon, Oslan Juliana; Tarigan, Miska Irani Br; Haloho, Elizabeth (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
Human resource management (HRM) in the field of marketing and sales is an essential aspect of achieving organizational goals. The process of employee rotation and promotion is often carried out based on managerial intuition, which can lead to subjectivity and unfair decision-making. This study aims to implement a Decision Support System (DSS) based on the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method to assist in the employee rotation and promotion process in an objective and systematic manner. The research methodology uses a quantitative approach with a case study in a company operating in the marketing sector. Data were collected through surveys, interviews with HR managers, and historical employee data analysis based on five key criteria: sales performance, creativity, communication skills, work experience, and loyalty. The findings indicate that the TOPSIS method provides accurate recommendations in determining the best candidates based on their relative proximity to the ideal solution. The analysis also identifies that sales performance is the most dominant factor in decision-making, with the highest weight of 35%. The implementation of a TOPSIS-based DSS enhances decision-making efficiency and accuracy while reducing subjectivity in the employee rotation and promotion process. The study concludes that this system can be an effective solution in supporting HR decision-making based on data-driven analysis and objective evaluation